The effects of individual differences on thermo-regulation in human body simulations - Celik, Nevin; Bayazit, Yilmaz (Turkish Soc Thermal Sciences Technology, 2008)
In recent years many models have been performed to investigate the thermo-regulation system of human body. In many of those models, a typical human body which is considered to represent the majority of the population is taken into consideration. However, ignoring some major factors such as the gender and the age, and minor factors, such as the surface of the body, the fat rate, height and weight of the person, the rate of O-2 that the person breaths, the color of the skin and the adaptation of the body to the climate, cause some errors at the result of the modeling. The individual differences topic which has impetus on the then-no-regulation system is needed to be held on by the researchers who have been studied on this scientific area. The missions of this paper are first to introduce the predone works about the mentioned topic by presenting the theoretical and empirical correlations, and second to emphasize some important factors which should be considered in the future models.
İnsan vücudunun modellenmesi?nde ki?şi?sel de?i?şi?kli?kleri?n termo-regülasyon üzeri?ndeki? etki?leri?
Keywords: bio-heat; thermoregulation; physiological data; individual differences